2015
DOI: 10.1186/s12936-015-0932-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and cost of using mobile phones for capturing drug safety information in peri-urban settlement in Ghana: a prospective cohort study of patients with uncomplicated malaria

Abstract: BackgroundThe growing need to capture data on health and health events using faster and efficient means to enable prompt evidence-based decision-making is making the use of mobile phones for health an alternative means to capture anti-malarial drug safety data. This paper examined the feasibility and cost of using mobile phones vis-à-vis home visit to monitor adverse events (AEs) related to artemisinin-based combination therapy (ACT) for treatment of uncomplicated malaria in peri-urban Ghana.MethodsA prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…For reports submitted by mobile phone, the average delay from case presentation to the notification reaching the central office was 24 h. In a study using SMS to monitor AEs after immunization in Australia, most patients who received an SMS query about adverse vaccine reactions sent a response within 2 h of receiving the query [ 16 ]. A study in Ghana, where the use of mobile phones to contact patients was compared with home visits to identify AEs related to artemisinin-based combination therapy for treating uncomplicated malaria found a slightly higher reporting rate with mobile phones, and that it was possible to interview the majority of patients within a few days [ 17 ]. In Uganda, an SMS-based reporting system for monitoring malaria diagnosis and treatment improved timeliness in data reporting [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For reports submitted by mobile phone, the average delay from case presentation to the notification reaching the central office was 24 h. In a study using SMS to monitor AEs after immunization in Australia, most patients who received an SMS query about adverse vaccine reactions sent a response within 2 h of receiving the query [ 16 ]. A study in Ghana, where the use of mobile phones to contact patients was compared with home visits to identify AEs related to artemisinin-based combination therapy for treating uncomplicated malaria found a slightly higher reporting rate with mobile phones, and that it was possible to interview the majority of patients within a few days [ 17 ]. In Uganda, an SMS-based reporting system for monitoring malaria diagnosis and treatment improved timeliness in data reporting [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study that is perhaps the closest to the present one in design is the INDEPTH study of a fixed-dose combination of dihydroartemisinin and piperaquine phosphate (Eurartesim ® ), conducted in four African countries between 2013 and 2014 [21], which included 11,097 patients with RDT-confirmed P. falciparum infections who were followed up by home visits from a CHW or by telephone. More recently, a study in Ghana of patients prescribed ACT [27] has compared telephone contact and home visits by a CHW and found that the former method elicited more AEs and was less expensive to implement. On the other hand, a Nigerian study with telephone monitoring which enrolled patients buying anti-malarials in a pharmacy reported that, for many patients, telephone contact was not maintained over time [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the introduction of newer technologies such as cell phones to report and investigate AEs to any medical products or certain specific therapeutic classes could provide added value. 44,[51][52][53] The latter could facilitate rapid identification of drug safety signals, provided that connectivity conditions are good.…”
Section: Discussionmentioning
confidence: 99%